Optics in Data Processing and Data Transmission - Frazão, João Manuel (2017)
Today optical systems are more and more important in data communications (optical fibers) and are also becoming important in data processing (optical and quantum computing) allowing for a fully optical communication  network where all signals will be processed and transmitted in the optical domain. This paper gives an overview of optical fiber communications and analyses some optical devices and applications such as optical computing, holographic memory and optical pattern recognition.